Исследование костюма золотоордынского времени из кургана 2 группы Токовские Могилы - Крупа, Т.Н. (Степи Европы в эпоху средневековья, 2008)
The paper is devoted to the complex research of costume fragments found in a burial in barrow 2 near Тokovskoie village on the Kamenka river (the Lower Dnieper basin).